The importance and the adaptation of internal resources as a competitive advantage for the internationalization of food companies: An analysis of Brazilian companies. Issue 3 (17th June 2019) - Pigatto, Gessuir; Santini Pigatto, Giuliana Aparecida; Satolo, Eduardo Guilherme; Negreti, Amanda dos Santos
Abstract : Purpose: The purpose of this paper is to analyze how Brazilian food companies in the State of São Paulo determine the importance of and the need to adapt their internal resources as a competitive advantage for internationalization. Design/methodology/approach: From a resource-based view (RBV), 35 different factors grouped into four categories were identified and presented to 24 companies. The data were analyzed through a gray relational analysis to establish all factors' order of importance. Findings: Factors linked to human and organizational resources present greater adaptability and allow companies competitive and sustainable advantages but have not yet been explored thoroughly. Identifying and adapting internal resources do not guarantee achieving competitive and sustainable advantages, as the access to international market is also a consequence of commercial agreements developed by countries and economic blocks. Practical implications: The analysis highlights the fragility of competitiveness among the companies analyzed in exporting products with commodity characteristics, with none or little differentiation. Such products are traded mainly through trading companies, which allow the access of the same market to internal competitors and other countries. Thus, any lapse promoted by the company may be enough for it to lose its competitiveness and, hence, market space. Originality/value: This paper stands out in the field of strategic management, specifically in the research on RBV, exportation and competitiveness, by making use of the theory of gray correlation system in an innovative and original way.